(untitled) (Patan Pragya, 2025)
This article serves as a guide for early-career researchers to understand foundational beliefs that inform research. It clarifies concepts by defining various research philosophies, including positivism, post-positivism, interpretivism, critical realism, and pragmatism, as well as related ideas like research paradigms, ontology, epistemology, axiology, design, and methodology. The impact of research philosophy on methodological choices for data collection and analysis is highlighted, using secondary data through meta-analysis. The paper covers key paradigms: Positivism emphasizes objective truths with quantitative methods; post-positivism acknowledges researcher influence; Interpretivism focuses on subjective meanings with qualitative methods; Constructivism views knowledge as socially constructed; Pragmatism uses mixed methods for practical solutions; and critical realism integrates positivism and interpretivism to uncover social structures. The article provides practical examples to guide project development.